2013
DOI: 10.1073/pnas.1307218110
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating mutations of RNF43 confer Wnt dependency in pancreatic ductal adenocarcinoma

Abstract: A growing number of agents targeting ligand-induced Wnt/β-catenin signaling are being developed for cancer therapy. However, clinical development of these molecules is challenging because of the lack of a genetic strategy to identify human tumors dependent on ligand-induced Wnt/β-catenin signaling. Ubiquitin E3 ligase ring finger 43 (RNF43) has been suggested as a negative regulator of Wnt signaling, and mutations of RNF43 have been identified in various tumors, including cystic pancreatic tumors. However, los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
383
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(403 citation statements)
references
References 42 publications
19
383
0
1
Order By: Relevance
“…The prevention of Wnt ligand secretion after treatment with WNT974 results in decreased phosphorylation of the surface receptor LRP6 and decreased expression of Wnt target genes like AXIN2. 16,17 WNT974 has shown anti-tumor activity in pancreatic adenocarcinoma and head and neck squamous cell cancer. Jiang et al 17 identified both WNT974 sensitive tumor cells and a potential predictive biomarker after demonstrating tumor growth inhibition through cell cycle arrest in in vivo pancreatic tumors treated with WNT974 with inactivating mutations in the RNF43 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevention of Wnt ligand secretion after treatment with WNT974 results in decreased phosphorylation of the surface receptor LRP6 and decreased expression of Wnt target genes like AXIN2. 16,17 WNT974 has shown anti-tumor activity in pancreatic adenocarcinoma and head and neck squamous cell cancer. Jiang et al 17 identified both WNT974 sensitive tumor cells and a potential predictive biomarker after demonstrating tumor growth inhibition through cell cycle arrest in in vivo pancreatic tumors treated with WNT974 with inactivating mutations in the RNF43 gene.…”
Section: Discussionmentioning
confidence: 99%
“…16 WNT974 has been shown to suppress growth of Wnt-driven tumors, such as pancreatic and head and neck squamous cell cancer with mutations in Wnt pathway modulators such as Ring finger 43 (RNF43). 17 The R-spondin (RSPO) protein family is comprised of four secreted growth factors. Secreted RSPO proteins activate Wnt/ β-catenin signaling, and RSPO mutations can further upregulate Wnt/β-catenin signaling.…”
mentioning
confidence: 99%
“…Recent studies (ref. 44; Madan and colleagues; unpublished data) have demonstrated that the proliferation of pancreatic cancer cell lines and patient-derived xenografts with inactivating RNF43 mutations is inhibited by PORCN inhibitors, including LGK974, Wnt-C59, and ETC-159. Hence, RNF43 and ZNRF3 mutations, by sensitizing cells to Wnts, may also be predictive of response to both PORCN inhibitors and Frizzled antibodies.…”
Section: Rnf43 and Znrf3 Loss-of-function Mutationsmentioning
confidence: 99%
“…8 RNF43 mutations have also been shown to confer Wnt dependency in pancreatic cancer cells. 9 However, the clinicopathological relevance of RNF43 mutations in intraductal papillary mucinous neoplasms remains unclear.…”
mentioning
confidence: 99%